A Double-Layer Optimization Maintenance Strategy for Photovoltaic Power Generation Systems Considering Component Correlation and Availability - Li, Xubin; Chen, Wei; Lei, Huan; Pei, Tingting; Pei, Xiping (Frontiers in Energy Research, 2022)
In view of the problem that the maintenance method based on the failure-independent condition of a photovoltaic power generation system during the maintenance cycle cannot effectively reflect the impact of the comprehensive correlation of the components on the maintenance strategy, and on the basis of the maintenance cost and the optimal availability, a new double-layer optimized maintenance strategy for photovoltaic power generation systems based on component correlation and availability is proposed. Firstly, the comprehensive correlation of the components in the system is analyzed, and then an upper-level optimization model is established based on this, with the goal of the lowest maintenance cost of the system. With the highest system availability as the goal and component availability as the constraint, a lower-level optimization model is established for verification. This strategy takes into account the influence of the component failure correlation and weather parameters. The influence of failure correlation on the maintenance strategy and system availability is verified by introducing failure-related strength, and weather accessibility is introduced to verify its influence on the maintenance cost and system availability change rate. Taking a photovoltaic power station in the west as an example, the results from comparing different maintenance plans show that the maintenance strategy proposed in this paper can effectively reduce maintenance costs and downtime, while increasing the system availability.